2017
DOI: 10.1080/10942912.2017.1352601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the cardioprotective effect of avocado consumption: A systematic review

Abstract: The objective of this review was to verify the effects of avocado consumption on cardiovascular diseases (CVDs) risk factors. A systematic search was conducted in electronic databases using the descriptor avocado, combined with CVD, monosaturated fat, antioxidant, lipoprotein, and inflammation, and their respective terms in Spanish. The review was carried out in pairs, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) recommendations. Initially, 234 studies were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…While the AFT and DSST scores were significantly better for avocado consumers in our unadjusted model, the significance was attenuated in the adjusted models. Given avocado consumption is growing dramatically worldwide, and research has shown the cardiometabolic benefits of eating avocados through the effects of various dietary components, phytochemical, and nutrients that avocados include as discussed by Silva Caldas et al (29)(30)(31)(32)(33)(34), it's relevant to study the cognitive benefits of avocado intake within a large population cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While the AFT and DSST scores were significantly better for avocado consumers in our unadjusted model, the significance was attenuated in the adjusted models. Given avocado consumption is growing dramatically worldwide, and research has shown the cardiometabolic benefits of eating avocados through the effects of various dietary components, phytochemical, and nutrients that avocados include as discussed by Silva Caldas et al (29)(30)(31)(32)(33)(34), it's relevant to study the cognitive benefits of avocado intake within a large population cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid is the major MUFA in avocado oil and probably one of the main components responsible for the beneficial effects attributed to avocado oil consumption. Oleic acid can decrease LDL by increasing acyltransferase activity to increase the synthesis of cholesterol esters, which stimulate the action of LDL receptors, favoring the LDL uptake and reducing its presence in plasma (Silva‐Caldas et al., 2017). In addition, a decrease of TG in plasma and an increase of high‐density lipoprotein cholesterol (HDL) may increase the hydrolysis of long‐chain fatty acids in TG by lipoprotein lipase, which are incorporated into HDL particles (Perona et al., 2010; Rashid et al., 2003).…”
Section: Effects Of Avocado Oil On Human Healthmentioning
confidence: 99%
“…In addition, a decrease of TG in plasma and an increase of high‐density lipoprotein cholesterol (HDL) may increase the hydrolysis of long‐chain fatty acids in TG by lipoprotein lipase, which are incorporated into HDL particles (Perona et al., 2010; Rashid et al., 2003). On the other hand, oleic acid induces lower endogenous TC synthesis (Silva‐Caldas et al., 2017), and therefore, avocado oil (rich in oleic acid) may also decrease TC and LDL. Other mechanisms possibly involved in the prevention of CVD by oleic acid include its anti‐inflammatory and vasculature protective activities by decreasing the expression of tumor necrosis factor alpha (TNF‐α) and interleukin‐6 (IL‐6) gene (Baer et al., 2004; Scoditti et al., 2015).…”
Section: Effects Of Avocado Oil On Human Healthmentioning
confidence: 99%
“…Weschenfelder et al () reported that avocado consumption seems to be related to cardiometabolic health by preventing traditional risk factors such as dyslipidemia, glycemic control and hypertension. Few studies have discussed the mechanisms through which antioxidants (polyphenols, tocopherols, vitamins, carotenoids), MUFA, fibre and phytosterols exert such beneficial effects (Silva‐Caldas et al , ). These studies however, were performed with animal models and therefore results should be interpreted with caution until studies in humans confirm the benefits of avocado consumption.…”
Section: Introductionmentioning
confidence: 99%